Экспериментальное исследование электрофизических параметров полиэтилентерефталатных пленок - Облакевич, Сергей Викторович; Хоминич, Виктор Иванович (НТУ "ХПИ", 2010)
Изложены результаты экспериментальных исследований характеристик полиэтилентерефталатной пленки. Определены структура покрытия пленки, толщина окисного слоя на нем. Получены значения удельного и поверхностного сопротивлений покрытия, его стойкости к электрическим разрядам. Приведены значения пробивного напряжения и пробивной напряженности для пленки. Сделана оценка надежности работы пленки.

Results of experimental tests of polyethylene-theraftalate (PET) films characteristics are given. The structure of the film coating and the thickness of its oxide layer are determined. Results and values of specific and superficial resistance of the coating and its resistance to electrical discharges are obtained. Values of breakdown voltage and breakdown stresses for PET films are revealed. Estimation of the film reliability degree is made.
Experimental tests of electrophysical parameters of polyethylene-theraftalate films
Keywords: ПЭТ-пленка; элементы космической техники; алюминиевое покрытие ПЭТ- пленки; тонкопленочные металлические проводники; dielectric polyethylene-theraftalate films; structure of coating; thickness of oxide layer; electrical discharges; breakdown voltages and stresses; reliability